Large-scale fabrication of ordered arrays of microcontainers and the restraint effect on growth of CuO nanowires - Shao Pengrui; Deng Shaozhi; Chen Jun; Xu Ningsheng (Nanoscale Research Letters, 2011)
Abstract Technique has been developed to fabricate ordered arrays of microcontainers. We report that ordered microcontainer arrays of Cu can be fabricated on glass substrate by thin film deposition and self-assembly technology. In addition, CuO nanowires are found to grow only in the inner sides of microcontainers, which verifies the stress growth mechanism of CuO nanowires. High-resolution transmission electron microscopy study reveals that CuO nanowires grow along the [110] direction. Such structure may have potential application in micro-electron sources, which have the self-focused function.